A strong basis for friction as the origin of size effect in cutting of metals. (September 2021) - Feng, Gan; Sagapuram, Dinakar
Abstract: A study has been made of the phenomenon of size effect in cutting of metals, namely increase in the specific energy with decreasing chip thickness, in the absence of edge radius effects and under ideal two-dimensional cutting conditions. Freshly cleaved glass knives are used to achieve cutting edges that are sharp on an atomic level. An instrumented ultramicrotomy apparatus is described in which it is possible to achieve two-dimensional orthogonal cutting at small cutting depths in the range of 100 nm to 3 micrometers. Based on observations with three metals (aluminum, copper and zinc), new evidence is presented in support of tool-chip friction as the primary source of the size effect. It is shown that size effect arises as a result of non-proportional decrease of the friction component with the underlying length scale. Calculation of the shear flow stress during cutting showed that this was approximately constant for a given material, independent of the depth of cut. Size dependence of tool-chip friction and contact size is interpreted in terms of the junction growth and adhesion models. Cutting experiments are also carried out with tools covered with solid and liquid contaminants. These results show that contaminant films effectively diminish adhesion and lead to a drastic reduction in the size effect, suggesting practical benefits for industrial manufacturing processes. Graphical abstract: Highlights: A large size effect occurs in cutting of ductile metals even in the absence of cutting edge radius effects. The size effect is characterized by up to 6-fold increase in the specific energy with decrease in the cutting depth. The size effect is caused by non-proportional scaling of tool-chip contact friction with the cutting depth. Tool contamination and surface films suppress the size effect, while reducing cutting forces by up to 70%. Linear extrapolation of cutting force data from higher depths into sub-micrometer length scales is inaccurate and leads to large errors.